The zinc finger protein Gfi-1 can enhance STAT3 signaling by interacting with the STAT3 inhibitor PIAS3 - Rödel, Bernd (Oxford University Press, 2000)
STAT factors act as signal transducers of cytokine receptors and transcriptionally activate specific target genes. The recently discovered protein PIAS3 binds directly to STAT3 and blocks transcriptional activation. Here, we present experimental evidence implementing the zinc finger protein Gfi-1 as a new regulatory factor in STAT3-mediated signal transduction. The interaction between the two proteins first became evident in a yeast two-hybrid screen but was also seen in coprecipitation experiments from eukaryotic cells. Moreover, we found that both Gfi-1 and PIAS3 colocalize in a characteristic nuclear dot structure. While PIAS3 exerts a profound inhibitory effect on STAT3-mediated transcription of target promoters, Gfi-1 can overcome the PIAS3 block and significantly enhances STAT3-mediated transcriptional activation. In primary T cells, Gfi-1 was able to amplify IL-6-dependent T-cell activation. As Gfi-1 is a known, dominant proto-oncogene, our findings bear particular importance for the recently described ability of STAT3 to transform cells malignantly and offer an explanation of the oncogenic potential of Gfi-1 in T lymphocytes.